Studies of modern music production and the methodical uses of metadata - McGarry, Glenn (2020)
Digital technology has played a central role in revolutionising the ways in which recorded popular music is both produced and consumed. This radical transformation, coined as the “mp3-crisis”, has been both devastating in its impact, and has opened up opportunities for art, technology, and business. The rise of file sharing platforms and the accessibility of digital production tools undermined both the music business’s model of distribution and models of music production leading to huge drops in revenue and a drastic reduction of the recording studio sector. Meanwhile, the emergence of digital marketplaces serving the supply chain are burgeoning, and the ‘democratisation’ of music-making digital tools has furthered the arts in allowing a broader range of people to engage in music-making.